Analysis of the Values of Religious Moderation in Malay Islam - Noor Hidayah; Maryamah Maryamah; Nanda Enita Virgianti; Sindy Febrianti (Sustainable, 2023)
Religious moderation is the practice of understanding and implementing religious teachings in a fair and balanced manner, aiming to prevent excessive and extreme behavior. It emphasizes the principles of wasatiyah (moderation), justice, and balance, aligning with the teachings of Islam that advocate for peace, tolerance, and unity. This study explores the integration of religious moderation values within Malay Islamic civilization, which is characterized by inclusivity, compassion, and adaptability. The spread of Islam in the Malay region was historically marked by its moderate, egalitarian approach, which facilitated its acceptance among diverse religious communities. Indonesia, as a nation built on Pancasila, embraces pluralism and multiculturalism, striving to maintain harmony and unity amidst its diverse cultural, ethnic, and religious landscape. This research employs a library research method, examining literature, journals, and scholarly works to analyze the principles of religious moderation and their application in education and social life. Key values such as tawassuth (middle path), tawazun (balance), i'tidal (justice), and tasamuh (tolerance) are identified as fundamental components of religious moderation. These values not only foster social cohesion but also align with the national ideals of unity and harmony. The study concludes that promoting religious moderation in education and daily life is essential for preventing conflict and fostering a peaceful, multicultural society, especially in the context of the diverse Indonesian nation.